Historie anielskie. Przyczynek do recepcji twórczości Władysława Broniewskiego = Angel stories. A contribution to the reception of Władysław Broniewski's works - Lisewska, Sławomira (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article discusses the reception of works by Władysław Broniewski. In recent years, interest in the poet has grown. In 1948, staying in Gorzów Wielkopolski, the artist wrote his epigram in an album. So far, neither Broniewski's diary nor his entry has been a subject of attention of researchers. The epigram text written in the album has been discussed and compared with the epigram text retained in the Władysław Broniewski's Museum and published versions of the short poem.
Keywords: recepcja; dokumenty; sztambuch; reception; document; album